2017
DOI: 10.1007/s00063-017-0362-1
|View full text |Cite
|
Sign up to set email alerts
|

Ich kann nicht mehr: Burn-out – eine Aufrüttelung

Abstract: Burnout is associated with a poor work environment. Burnout prevention or reduction is an important task which demands a multidimensional approach. The goal should be to improve the work environment, achieve good team collaboration, psychological safety, and inclusive leadership.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
0
6
0
3
Order By: Relevance
“…Neste estudo, foram identificados fatores restritivos e facilitadores que influenciam a prática das equipes como por exemplo, a sobrecarga identificada em todos os níveis de atenção à saúde. Pouca colaboração trabalho, excesso de demandas, comunicação prejudicada entre equipe e gestão inapta influenciam na insatisfação de profissionais com o seguimento do trabalho na assistência (24) . Condições inadequadas no ambiente de trabalho, relacionadas aos recursos financeiros, humanos e materiais, implicam na atenção aos usuários e famílias atendidas.…”
Section: Discussionunclassified
“…Neste estudo, foram identificados fatores restritivos e facilitadores que influenciam a prática das equipes como por exemplo, a sobrecarga identificada em todos os níveis de atenção à saúde. Pouca colaboração trabalho, excesso de demandas, comunicação prejudicada entre equipe e gestão inapta influenciam na insatisfação de profissionais com o seguimento do trabalho na assistência (24) . Condições inadequadas no ambiente de trabalho, relacionadas aos recursos financeiros, humanos e materiais, implicam na atenção aos usuários e famílias atendidas.…”
Section: Discussionunclassified
“…En este estudio, se identificaron factores restrictivos y facilitadores que influyen en la práctica de los equipos, como la sobrecarga de trabajo en todos los niveles de atención de la salud. La poca colaboración en el trabajo, las excesivas demandas, la mala comunicación dentro del equipo y una gestión inadecuada influyen en la insatisfacción que tienen los profesionales con el seguimiento del trabajo en la asistencia (24) . Condiciones inadecuadas en el ambiente de trabajo, relacionadas con los recursos financieros, humanos y materiales, afectan la atención a los usuarios y a las familias.…”
Section: Discussionunclassified
“…In this study, restrictive and facilitating factors that influence the teams’ practice were identified, such as the overload identified at all health care levels. Little collaboration work, excessive demands, impaired communication among the team members and unsuitable management exert an influence on the professionals’ dissatisfaction with the follow-up of work in care 24 . Inadequate conditions in the work environment related to financial, human and material resources imply attention to the users and families cared for.…”
Section: Discussionmentioning
confidence: 99%